Bahasa Indonesia Bahasa Indonesia - Herawati; Andhy Setiawan; Arif Hidayat (Postgraduate, University of Mataram, 2023)
Farmer is a Physics learning media that functions as Learning Management System (LMS) to organize, manage, and deliver subject matter on the concept of energy and its changes related to work, changes in mechanical, chemical, electrical, heat and renewable energy on the basic techniques of plant production processes which refer to a science literacy-based learning flow with a web format for the vocational school of Agriculture. The purpose of this study was to analyze the concept of Energy and its changes in Agriculture that are used in the LMS Farmer. The Material of Energy and its changes in Agriculture in LMS farmers were developed using the ADDIE model 1) Analysis Phase; 2) Design Phase; 3) Developed Phase; 4) Implementation Phase; 5) Evaluation Phase. This research used the qualitative method. The non-test research instruments included material validations by four material experts consisting of two physics experts, one teacher and one Agricultural material expert. The data analysis techniques included descriptive statistics. The results showed that the material of Energy and its changes in Agriculture on LMS Farmer, based on the assessment by four experts lies in the â€œfeasibleâ€ category. The conclusion of this study is that the material ofÂ Energy and its changes LMS Farmer in the feasible category so that they are feasible to be applied in physics learning for vocational schools majoring in Agriculture. Â